Dopamine receptor cooperativity synergistically drives dyskinesia, motor behavior, and striatal GABA neurotransmission in hemiparkinsonian rats. (1st September 2020) - Kiessling, Corinne Y.; Lanza, Kathryn; Feinberg, Evan; Bishop, Christopher
Abstract: The striatum undergoes significant neuroplasticity both in Parkinson's Disease (PD) and following dopamine (DA) replacement therapy with l -DOPA. Unfortunately, these changes also contribute to the emergence of l -DOPA-induced dyskinesia (LID). While convergent strategies have demonstrated independent roles for DA D1 -receptors (D1R) and D2-receptors (D2R) in LID, DA receptor cooperativity, either by cellular or circuit mechanisms, has also been implicated in the dyskinetic brain. How this cooperativity is substantiated is vitally important given that l -DOPA, once converted to DA, stimulates all DA receptors. The present experiments sought to characterize the effect of individual or collective stimulation of D1R and D2R-like receptors both systemically and intrastriatally. In experiment 1, hemiparkinsonian l -DOPA-primed rats received systemic doses of the D1R agonist SKF38393 and D2R-like agonist quinpirole. Dyskinesia and motor improvement were monitored using the abnormal involuntary movements scale (AIMs) and the forepaw adjustment steps test (FAS), respectively. In experiment 2, SKF38393 and quinpirole were administered intrastriatally via reverse-phase in vivo microdialysis while coincident changes in striatal glutamate and gamma-Aminobutyric acid (GABA) were monitored. SKF38393 and quinpirole dose-dependently increased AIMs. When threshold DA agonist doses were co-administered, AIMs and motor performance were synergistically enhanced. Like systemic experiments, striatal co-administration of threshold concentrations of DA agonists resulted in synergistic exacerbation of AIMs, and concurrent increases in GABA efflux. These data highlight the role of striatal DA receptor cooperativity in LID and suggest a central role for striatal GABA release in these effects. Highlights: Systemic dopamine D1 receptor and dopamine D2-like receptor agonists cooperate to drive dyskinesia and motor behaviors. Intrastriatal administration via reverse-phase microdialysis results in the synergistic exacerbation of dyskinesia. Synergistic dyskinesia expression following intrastriatal administration is marked by concurrent elevations in GABA.